The impact of healthcare delivery configuration on patients’ perceived service quality: Mediating roles of patient partnership and trust in Nanning, China - Haohai, Wang; Rehman, Asad Ur; Nawal, Ayesha; Khan, Waris Ali; Ullah, Ihtisham (Edelweiss Applied Science and Technology, 2026)
In the evolving landscape of modern healthcare, the mere provision of medical resources is insufficient to guarantee patient satisfaction. Understanding the internal mechanisms that translate structural configurations into perceived quality is crucial for hospital management. This study explores the impact of Healthcare Delivery Configuration (HDC) on Perceived Service Quality (SQ) within the medical context of Nanning, China. Based on the Stimulus-Organism-Response (SOR) theory and the SERVQUAL model, this research proposed a dual-pathway mediation framework. Data were collected from patients in various healthcare institutions, and structural equation modeling (SEM) combined with the bootstrap resampling method was employed to test the hypotheses and mediating effects. The empirical results indicate that HDC has a significant direct positive impact on SQ (beta = 0.525, p < 0.001). Furthermore, the mediation analysis confirms that Patient Partnership (PP) and Patient Trust (PT) play significant partial mediating roles. The indirect effect through the trust pathway was estimated at 0.131 (95% CI: [0.074, 0.198]), while the combined mediating pathways account for approximately 45% of the total effect (0.656). The findings suggest that while technical and structural optimizations are fundamental, their impact on service quality is significantly amplified when they foster collaborative doctor-patient partnerships and strengthen emotional trust. Healthcare providers should not only focus on physical resource allocation but also prioritize building communication platforms that empower patients and consolidate trust to maximize perceived service quality in resource-constrained environments.